Modelagem hidrossedimentológica na sub-bacia do riacho Jacaré no baixo São Francisco sergipano - Macedo, Fabrício Lopes de (2010)
The quantification of sediment production, released by the basin, assists in proposing methods, whose main purpose is to guide farmers, that will use natural resources in a sustainable way, aiming at the least possible degradation the areas used. Since the production of food, most often happens in an unplanned way in which almost all native vegetation is removed, it theoretically has no purpose in view of most farmers. However, the vegetation is considered by many researchers as the main barrier against the processes of land degradation, particularly for the control of erosion. This study aimed to simulate the sediment yield in the Sub-Basin of Riacho Jacaré, using the methodology of this MUSLE (Universal Soil Loss Equation Soil Modified).